2011
DOI: 10.5754/hge11060
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Gallstones and Related Risk Factors in Iran

Abstract: The prevalence of gallstone disease in Iran is low. There was a positive correlation between prevalence of gallstone with age, BMI, diabetes mellitus and number of parity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…Agunloye et al 65 found that the incidence of gallstones in patients with T2DM was closely related to the course of DM, through abdominal ultrasonography in 400 patients with T2DM. Toosi et al 66 also proposed that the prevalence of gallstones was positively correlated with the course of DM. Most patients with DM complicated with gallstones have no obvious discomfort symptoms.…”
Section: Gallstonesmentioning
confidence: 98%
“…Agunloye et al 65 found that the incidence of gallstones in patients with T2DM was closely related to the course of DM, through abdominal ultrasonography in 400 patients with T2DM. Toosi et al 66 also proposed that the prevalence of gallstones was positively correlated with the course of DM. Most patients with DM complicated with gallstones have no obvious discomfort symptoms.…”
Section: Gallstonesmentioning
confidence: 98%
“…Studies have shown that diabetes is one of the high risk factors International Journal of Clinical Medicine for gallbladder disease, such as gallstones, gallbladder polyps, gallbladder cancer, etc. [3] [4] [5]. The incidence of gallstones is higher in diabetic patients.…”
Section: Diabetes and Gallstonesmentioning
confidence: 99%
“…Its prevalence is less than 5% in African countries, 3 and 15% in North American population. 4 In Iran, the prevalence of GSD was reported to be about 0.8% in Amol, 5 2.5% in Birjand, 6 and 4.7% in Southern Iran. 7 Risk factors for GSD have been described in previous epidemiological reports and obesity and hyperinsulinemia are the most related of these.…”
Section: Introductionmentioning
confidence: 99%